Preaching as the Convergence of the Vanishing Point between Reality and Imagination: Exploring the Reciprocity between Remembrance and Imagination - Ferdi P. Kruger (International Journal of Homiletics)
The inquiry posed in this research seeks to answer the question: “How can a homiletical praxeology focused on imagination enhance one's understanding of their remembrances to see and reason about invisible aspects communicated to them?” Employing a qualitative-hermeneutical approach that integrates descriptive and theological perspectives, this question is addressed retrospectively. The focus is on the convergence between reality and imagination and the distinctive contribution of preaching in this context. The investigation delves into the nuanced examination of two powerful legs of a homiletical praxeology – remembrance (anamnesis) and imagination. The dynamic act of remembrance involves the intricate assembly of fragmented memories from the gospel and daily life, underscoring its paramount significance. The exploration extends to the essential dynamic of meaning-making (Sinndeutung), asserting that preaching, dealing with remembrance and imagination, provides a vital aperture for listeners to participate in this endeavour actively. While liturgy furnishes a distinctive framework enabling preachers and listeners to operate on the same eye level when contemplating the vanishing point, the dynamic interplay of remembrance and imagination, influenced by what listeners have remembered, might deviate from the preacher's initial expectations. Despite potential disparities, it is contended that a preacher deeply connected to remembrances of the gospel and adept at reimagining counteractive alternatives in the passage can effectively enable listeners to remember vividly with an eye on imagination.